The Effect of Work Commitment and Organizational Culture on Employee Performance with Work Environment Mediation (Case Study of PT PLN Indonesia Power UBP Barito in South Kalimantan) - Dedy Putro Triyuwono; Sulastini; Dwi Wahyu Artiningsih (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
In the era of industrial transformation and digitalization in the energy sector, the success of public organizations such as PT PLN Indonesia Power UBP Barito increasingly depends on employees who demonstrate strong commitment and a positive work culture. The study aims to examine the influence of employee commitment and organizational culture on employee performance and to analyze the mediating role of the work environment in this relationship. This study employed a quantitative approach with an explanatory design. The population consisted of 130 employees of PT PLN Indonesia Power UBP Barito, from which 98 respondents were selected as the sample using the Slovin formula. Data were collected through a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS version 4. The findings indicate that employee commitment and organizational culture have a positive and significant effect on employee performance. Furthermore, the work environment was found to partially mediate the relationship between both independent variables and performance. These results highlight that strong employee commitment, a positive organizational culture, and a supportive work environment collectively enhance employee effectiveness and performance at PT PLN Indonesia Power UBP Barito